Understanding Meditation Based on the Subjective Experience and Traditional Goal: Implications for Current Meditation Research - Reddy, J. Shashi Kiran; Roy, Sisir (Frontiers in Psychology, 2019)
Owing to its benefits on various cognitive aspects, one’s emotions and wellbeing, meditation has drawn interest from several researchers and common public alike. We have different meditation practices associated with many cultures and traditions across the globe. Current literature suggests significant changes in the neural activity among the different practices of meditation, as each of these practices contributes to distinct physiological and psychological effects. Although this is the case, we want to find out if there is an underlying commonality among all these different practices. So, we ask the following questions related to different practices of meditation, the traditional goal of meditation and its significance - What is the central purpose of meditation? Do traditions define the final goal of all the practices of meditation? Are the purpose and goal of these practices different or is there a common goal to be attained through all these distinct practices? Embracing the traditional perspective, through this paper, we want to emphasize, although these techniques and practices may appear different on the periphery, eventually, they seem to subject one to the same experience at the end; a natural meditative state (discussed in various spiritual traditions as the goal of meditation). In view of future studies on different meditation practices and also those exploring this subjective state, we offer some interesting ideas based on the traditional insights on meditation. In this context, we would also like to make a few comments on the way contemporary researchers view different practices of meditation.